PEMAKNAAN JILBAB DAN IDENTITAS MUSLIMAH ( Studi tentang âHijabers Communityâdi Yogyakarta) - , BUDIANI R S; , Dr. Suharko ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The wearing of Jilbab, also known as veil, is not only about fashionor looks. As we all know, jilbab is a symbol of values and traditions of Islam. However, current facts shows that there are several moslem women that interpret and represents the wearing of jilbab as more than just an obligation of Islamic value, and more towards the modernization, regarding the phenomenon of fashionable moslem women. On their daily life,the moslem women had a certain attention towards their looks, such as the jilbab and dressing style. This is due to a number of factors that affect a moslem women to have a fashionablelooks, such as, the tendency of wearing jilbab style that attracts attention, which then mimicked by other moslem women. Behind their fashionable looks, moslem women has a meaningful identity. Through their jilbab and dress, they show the image of the wearer, such as neatness, courtesy, and a symbol of piety as a moslem woman. Jilbab is represented as a part of todays fashionable moslem women lifestyle, as well as an image of moslem women community, by using it as a media in conveying Islamic values. Hijabers Community Yogyakarta (HCY) through values and norms, represents the identity of moslem women, which is pious towards Islamic value in a modern form, through the practice of fashionablejilbab style. This research uses qualitative approach with the objective of understanding current phenomenon. This research attempts to answer the problems of HCY community in interpreting jilbab as Islamic symbol and as a collective identity, by using the theory of representation and identity from Stuart Hall, and how the HCY community represents fashionable moslem women identity as a part of todays lifestyle.